2017
DOI: 10.21037/qims.2017.12.02
|View full text |Cite
|
Sign up to set email alerts
|

Weight bearing cone beam CT scan versus gravity stress radiography for analysis of supination external rotation injuries of the ankle

Abstract: For AO 44-B2 ankle fractures of uncertain stability, the current diagnostic standard is to obtain a gravity stress radiograph, but some have advocated for the use of weight-bearing radiographs. The primary aim was to compare measures of medial clear space (MCS) on weight-bearing cone beam computed tomography (CBCT) scans versus gravity stress radiographs for determining the state of stability of ankle fractures classified as AO SER 44-B2 or Weber B. The secondary aim was to evaluate the details offered by CBCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…We have found that, like plain radiography, weight-bearing CT scans can indicate stability in many SER fractures of uncertain status and could be used to select patients for nonoperative treatment based on medial clear space measurement. 18 On the other hand, we also noticed by examining all 3 planes of CT images that there was rarely perfect reduction, with residual fibular shortening, fibular rotation, fracture comminution, and asymmetry of the distal tibiofibular joint present. We are not certain of the clinical implications of these findings, and although others have shown good clinical outcome when only medial clear space is used for decision making, the studies have been of relatively short follow-up.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We have found that, like plain radiography, weight-bearing CT scans can indicate stability in many SER fractures of uncertain status and could be used to select patients for nonoperative treatment based on medial clear space measurement. 18 On the other hand, we also noticed by examining all 3 planes of CT images that there was rarely perfect reduction, with residual fibular shortening, fibular rotation, fracture comminution, and asymmetry of the distal tibiofibular joint present. We are not certain of the clinical implications of these findings, and although others have shown good clinical outcome when only medial clear space is used for decision making, the studies have been of relatively short follow-up.…”
Section: Discussionmentioning
confidence: 81%
“…20,26 Previous studies, however, have demonstrated that gravity stress radiographic measurements may overestimate the number of patients in need of operative fixation. 11,13,14,18,27,31 These authors report that weight-bearing radiographs are more predictive of stability, and patients with an anatomic mortise relationship can be successfully managed with immediate protected weight bearing and functional rehabilitation, without having to undergo an operative procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the recent cone-beam CT (CBCT) technology, originally for the field of dentomaxillofacial radiology (15,(22)(23)(24), has proved to be also suitable to musculoskeletal radiology for upper and lower limb joints, and features reduced radiation dose, high surface and model accuracy (25,26), but mainly weight-bearing condition for the patient during scanning. These devices finally allow to study bone and joint architecture of the extremities under physiological load (14,(27)(28)(29)(30). Because of the limited field of view (FOV), the CBCT is thus suitable for joints of small dimension (27).…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Marzo et al 16 were the first to investigate the weightbearing CT scan, in comparison with the GS radiograph. Mean MCS on weightbearing CT scan (1.41 mm) was significantly less than that on standard radiographs (3.28 mm) and GS radiographs (5.82 mm).…”
Section: Introductionmentioning
confidence: 99%